Prolonged apnea in a boy with epilepsy and a novel gain-of-function missense CACNA1A variant indicating SUDEP risk - Pelizzari, Simone; Campiglio, Marta; El Ghaleb, Yousra; Bierhals, Tatjana; Hempel, Maja; Denecke, Jonas; Flucher, Bernhard E.; Johannsen, Jessika (Frontiers in neurology, 2025)
IntroductionThe CACNA1A gene encodes the pore-forming subunit of the Cav2.1 (P/Q type) neuronal calcium channel and pathogenic variants cause a variety of neurological disorders including episodic and congenital ataxia, familial hemiplegic migraine, developmental delay and epilepsy. Multiple types of seizures have been described in affected patients, including status epilepticus as the first manifestation. In mice harboring the homozygous gain-of-function variant p.Ser218Leu, seizures leading to SUDEP triggered by brainstem spreading depolarization with subsequent apnea and cardiac arrest have been reported.MethodsClinical, genetic and functional data are presented.Results and discussionThe 9-year-old boy with global developmental delay and congenital ataxia developed recurrent seizures and status epilepticus with prolonged, life-threatening apnea implying a high risk for SUDEP. Genetic testing showed a novel de novo missense variant in CACNA1A (c.5398T>A, p.Phe1800Ile). Functional analysis revealed a gain of channel function as the molecular pathomechanism. Therefore, an increased risk of SUDEP in patients with CACNA1-associated epilepsy seems reasonable and preventive strategies should be discussed with caregivers.
Veröffentlicht: 09. Juli 2025
Gesehen am 24.11.2025